An anti-icing coating with both photothermal and electrothermal properties and its preparation method and application

By using the collaborative coupling technology of expandable graphite and microspheres modified by linear polyconductive organic monomer in the ice-resistant coating, a three-dimensional porous lipophilic anti-ice coating with excellent photothermal and electric thermal properties was prepared, which solved the shortcomings of the existing coating in terms of cost, environmental protection and durability, and achieved efficient and economical anti-ice effect.

CN117025087BActive Publication Date: 2025-03-07TSINGHUA UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310926709.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-03-07
Estimated Expiration
2043-07-26

AI Technical Summary

Technical Problem

The existing ice-resistant coatings have shortcomings in terms of cost, environmental protection and durability, and the preparation process is complex, making it difficult to meet the requirements of industrial applications.

Method used

The conductive network is prepared by using expandable graphite modified with linear poly first conductive organic monomer and co-coupled with expandable microspheres modified with linear poly second conductive organic monomer to prepare a three-dimensional porous lipophilic anti-ice coating with excellent photothermal and electrothermal properties.

Benefits of technology

Efficient preparation of ice-resistant coatings on the surface of commonly used substrates is achieved, which significantly reduces ice adhesion strength, delays icing time, and improves the robustness and durability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117025087B_ABST
    Figure CN117025087B_ABST
Patent Text Reader

Abstract

The present application proposes an anti-icing coating with both photothermal and electrothermal properties, and its preparation method and application, wherein the preparation method of the anti-icing coating includes: modifying expandable graphite with a first conductive organic monomer, and then performing a first dispersion to obtain a colloidal liquid; electroplating a porous template with the colloidal liquid as an electrolyte, and then etching away the porous template to obtain a conductive network; modifying expandable microspheres with a second conductive organic monomer, and then performing a second dispersion in a high-temperature curing resin to obtain a dispersion; placing the conductive network on the surface of the substrate, and distributing the dispersion on the conductive grid and the substrate, and then heating and expanding, heating and shrinking, and cooling in sequence to obtain a three-dimensional porous coating; distributing an oily liquid on the surface and inside of the three-dimensional porous coating to obtain an anti-icing coating. The preparation method of the anti-icing coating of the present application can obtain a three-dimensional porous oleophilic anti-icing coating with excellent photothermal and electrothermal properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional material technology, and in particular to an anti-icing coating having both photothermal and electrothermal properties, and a preparation method and application thereof. Background Art

[0002] In various fields such as aviation, power transportation, communications, and ground transportation, icing has a very adverse impact on industrial facilities including transportation systems, telecommunications systems, and energy systems, often causing catastrophic safety problems and huge economic losses.

[0003] Current anti-icing / de-icing strategies mainly include active and passive methods. Active de-icing mainly includes active ice melting and de-icing achieved by using traditional chemical agents (melting agents), thermal forces (steam heating and electric heating ice melting), mechanical forces (mechanical vibration) and other methods. However, this active de-icing strategy is often accompanied by high costs and complex system designs, and many methods are considered to be environmentally unfriendly.

[0004] On this basis, in the past decade, zero-energy passive anti-icing / de-icing materials and surfaces have received great attention. Various means are used to construct materials and surfaces that can repel water droplets, inhibit ice formation, and reduce ice adhesion to prevent ice formation. These means mainly include the following three methods:

[0005] (1) Superhydrophobic structure or coating; Combined with the various stages of the freezing process, supercooled droplets first wet the solid surface and then quickly freeze into ice. In this case, the superhydrophobic surface can be called an ideal anti-icing surface: on the one hand, it can remove supercooled droplets by simply tilting the surface, bouncing the droplets off the surface, etc., reducing the probability of nucleation on the surface; on the other hand, the heat transfer between the coating surface and the supercooled droplets is significantly inhibited, thereby reducing the freezing temperature and delaying the freezing time. However, most of the current superhydrophobic coatings are brittle, and due to the low adhesion of low surface energy materials, they are susceptible to various mechanical damages such as peeling, wear, dynamic impact, etc., and the preparation process is generally more complicated and cannot meet the strict requirements of industrial applications.

[0006] (2) Using hygroscopic polymers to prepare highly hydratable ice-repellent coatings and hydrogels. The water-containing lubricating layer can significantly reduce the adhesion of ice, thereby inhibiting ice accumulation under wind. However, the preparation process of such coatings or gels is relatively complicated and they are easily damaged in humid or other extreme climates.

[0007] (3) Smooth liquid injected into porous surfaces. For example, researchers have developed a series of smooth porous surfaces and waxy organic gels injected with lubricants by imitating the smooth leaves of terrestrial plants (such as pitcher plants). These materials can significantly reduce the adhesion of ice, making it easy to separate the attached ice by gravity or airflow. However, this method faces the disadvantages of expensive injected lubricants, easy damage due to mechanical wear or multiple icing / deicing cycles, and the need for frequent maintenance and re-oiling, which limits its practical application. Summary of the invention

[0008] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0009] To this end, one object of the present application is to provide a method for preparing an anti-icing coating having both photothermal and electrothermal properties. The method is based on the synergistic coupling of a conductive network prepared from expandable graphite modified by a linear poly first conductive organic monomer and expandable microspheres modified by a linear poly second conductive organic monomer, so as to obtain a three-dimensional porous oleophilic anti-icing coating having excellent photothermal and electrothermal properties.

[0010] Another object of the present application is to provide an anti-icing coating.

[0011] Yet another object of the present application is to provide an application of an anti-icing coating.

[0012] To achieve the above-mentioned purpose, the first embodiment of the present application provides a method for preparing an anti-icing coating having both photothermal and electrothermal properties, comprising:

[0013] The expandable graphite is modified with a first conductive organic monomer, and then a first dispersion is performed to obtain a colloidal liquid;

[0014] Using the colloidal liquid as an electrolyte, electroplating the porous template, and then etching away the porous template to obtain a conductive network;

[0015] The expandable microspheres are modified with a second conductive organic monomer and then second dispersed in a high temperature curing resin to obtain a dispersion;

[0016] Placing the conductive network on the surface of a substrate, distributing the dispersion on the conductive network and the substrate, and then heating to expand, heating to shrink, and cooling in sequence to obtain a three-dimensional porous coating;

[0017] The oily liquid is distributed on the surface and inner pores of the three-dimensional porous coating to obtain the anti-icing coating.

[0018] In order to achieve the above-mentioned purpose, a second aspect of the present application provides an anti-icing coating, which is prepared by the preparation method of the embodiment of the present application.

[0019] To achieve the above-mentioned purpose, the third aspect of the present application relates to the application of the anti-icing coating in the fields of electricity, transportation, communication or aviation.

[0020] The method for preparing the anti-icing coating of the embodiment of the present application can at least bring the following beneficial effects:

[0021] The preparation method of the anti-icing coating of the embodiment of the present application is based on the synergistic coupling of the conductive network prepared by the expandable graphite modified by the linear poly first conductive organic monomer and the expandable microspheres modified by the linear poly second conductive organic monomer, and a three-dimensional porous oleophilic anti-icing coating with excellent photothermal and electrothermal properties can be obtained. The method mainly combines the active and passive modes, that is, the photothermal conversion of the expandable microspheres modified by the linear poly second conductive organic monomer with the photothermal effect, the electrothermal effect of the conductive network made of the expandable graphite modified by the linear poly first conductive organic monomer, and the low ice adhesion characteristics caused by the porous oleophilicity of the coating itself, and can be prepared on the surface of common substrates (such as AL, GCr15, stainless steel, fiberglass, etc.). The electrothermal and photothermal effects can be combined with the oil film produced by the preparation process of the coating itself by regulating the temperature change of the surface to greatly reduce the ice adhesion strength of the surface and delay the freezing time. At the same time, due to the high affinity of the three-dimensional porous structure and the high temperature curing resin itself to the selected oil, the oil can be stored for a long time, which greatly improves the robustness of the low ice adhesion performance of the coating.

[0022] The anti-icing coating and the application of the anti-icing coating in the embodiments of the present application at least have the beneficial effects of the method for preparing the anti-icing coating in the embodiments of the present application.

[0023] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:

[0025] Figure 1 This is a flow chart of a method for preparing an anti-icing coating according to an exemplary embodiment of the present application.

[0026] Figure 2 It is a physical comparison diagram of the expandable graphite (flake graphite) in Example 1 expanding into a worm-like graphite line, wherein: a is a physical diagram of the expandable graphite (flake graphite), and b is a physical diagram of the worm-like graphite line.

[0027] Figure 3 This is a physical picture of the linear Ppy-modified worm-like porous graphite wire L-Ppy-EG in Example 1.

[0028] Figure 4 These are physical comparison pictures of the linear polypyrrole-modified graphite wire conductive network in Example 1 at different angles, where: c is a physical picture at a frontal angle, and d is a physical picture at a side angle.

[0029] Figure 5 is the resistance test value of the linear polypyrrole modified graphite wire conductive network in Example 1.

[0030] Figure 6 The linear polypyrrole-modified expandable microspheres L-Ppy-EM in Example 1 and scanning electron microscope (SEM) test images at different scales, wherein: e is a real image of L-Ppy-EM, f is a scanning electron microscope (SEM) test image at a scale of 20 μm, g is a scanning electron microscope (SEM) test image at a scale of 20 μm, and h is a scanning electron microscope (SEM) test image at a scale of 2 μm.

[0031] Figure 7 It is a physical picture of the conductive three-dimensional porous coating in Example 1 and a scanning electron microscope picture characterizing the cross-sectional porous structure, wherein: i is a physical picture of the conductive three-dimensional porous coating, j is a cross-sectional porous picture at a scale of 300 μm, and k is a cross-sectional porous picture at a scale of 300 μm.

[0032] Figure 8 This is a comparison chart of the electrothermal performance characterization of the anti-icing coating in Example 1.

[0033] Fig. 9 Schematic diagram of the homemade ice adhesion testing equipment.

[0034] Fig.10 This is a comparison chart of the ice adhesion strength of the anti-icing coating prepared in Example 1.

[0035] Fig.11 This is a comparison chart of the ice adhesion strength of the anti-icing coating prepared in Example 2.

[0036] Fig.12 This is a characterization diagram of the photothermal performance of the anti-icing coating in Example 1.

[0037] Fig.13 The low ice adhesion performance robustness of the anti-icing coating in Example 1.

[0038] Fig.14 This is the conductivity test of the anti-ice coating sample of Comparative Example 1.

[0039] Fig.15 This is the light and thermal performance test of the anti-ice coating sample of comparative example 1.

[0040] Fig.16 This is a resistance test data diagram of the anti-icing coating prepared in Example 1.

[0041] Fig.17 This is a resistance test data diagram of the anti-icing coating prepared in Comparative Example 2.

[0042] Fig.18 This is a comparison chart of the electrothermal performance characterization of the coating prepared in Comparative Example 2.

[0043] Fig.19 These are scanning electron microscope images characterizing the cross-sectional porous structures in Example 8, Example 9, Comparative Example 5 and Comparative Example 6, wherein: (a) is a scanning electron microscope image characterizing the cross-sectional porous structure in Example 8; (b) is a scanning electron microscope image characterizing the cross-sectional porous structure in Example 9; (c) is a scanning electron microscope image characterizing the cross-sectional porous structure in Comparative Example 5; and (d) is a scanning electron microscope image characterizing the cross-sectional porous structure in Comparative Example 6.

[0044] Fig. 20 This is a test diagram of the lipophilicity of the anti-icing coating prepared in Example 1.

[0045] Reference numerals:

[0046] 1-environmental temperature control cabinet; 2-sample; 3-icing icicle model; 4-stepping push rod; 5-cooling table; 6-driving unit. DETAILED DESCRIPTION

[0047] The embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, but cannot be understood as limiting the present application.

[0048] Throughout the application, the disclosure of numerical ranges includes all values ​​within the entire range and disclosure of further subdivided ranges, including endpoints and subranges given within those ranges.

[0049] In the application, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be produced through commercial channels or known methods; the methods involved, unless otherwise specified, are all conventional methods.

[0050] A method for preparing an anti-icing coating according to an embodiment of the present application is described below with reference to the accompanying drawings.

[0051] Figure 1 This is a flow chart of a method for preparing an anti-icing coating according to an exemplary embodiment of the present application.

[0052] like Figure 1 As shown, the method for preparing the anti-icing coating of the embodiment of the present application comprises the following steps:

[0053] S101, modifying expandable graphite with a first conductive organic monomer, and then performing a first dispersion to obtain a colloidal liquid.

[0054] In some embodiments, the first conductive organic monomer includes but is not limited to at least one of pyrrole, aniline, phenylacetylene, etc., preferably pyrrole.

[0055] In some embodiments, the expandable graphite includes but is not limited to flake graphite. As an optional example, the expandable graphite is flake graphite with a size of 75 μm.

[0056] In some embodiments, the method of modifying expandable graphite with a first conductive organic monomer comprises the following steps:

[0057] S1, performing a first expansion on expandable graphite to obtain a worm-like porous graphite wire;

[0058] S2, dispersing the worm-like porous graphite wires in a first acidic solution containing a first template, then performing a first cooling, and adding a first conductive organic monomer to obtain a solution A;

[0059] S3, adding the first accelerator to the second acidic solution to obtain solution B;

[0060] S4, subjecting solution A and solution B to a first polymerization reaction to obtain a worm-like porous graphite wire modified by a linearly polymerized first conductive organic monomer.

[0061] It should be noted that in the method of modifying expandable graphite with the first conductive organic monomer, the order of step S3 and step S1, and the order of step S3 and step S1 can be interchanged.

[0062] In some embodiments, the temperature of the first expansion is 300-400°C, including but not limited to 300°C, 320°C, 350°C, 370°C or 400°C.

[0063] In some embodiments, the content of the first template in the third dispersed dispersion (the first acidic solution containing the first template) is 0.3-1 wt.%, including but not limited to 0.3 wt%, 0.5 wt%, 0.8 wt% or 1 wt%, etc.

[0064] In some embodiments, the mass ratio of the worm-like porous graphite wire to the first template is (500-700):33, including but not limited to 500:33, 550:33, 600:33, 650:33 or 700:33, etc.

[0065] In some embodiments, the amount of the worm-like porous graphite wire and the first conductive organic monomer is in the following relationship: 500-700 mg of the worm-like porous graphite wire per 100 μl of the first conductive organic monomer. As a non-limiting example, the amount of the worm-like porous graphite wire per 100 μl of the first conductive organic monomer includes but is not limited to 500 mg, 550 mg, 600 mg, 650 mg or 700 mg. When the amount of worm-like porous graphite wire corresponding to every 100 μl of the first conductive organic monomer is within the above range, worm-like porous graphite wire with relatively good conductivity can be obtained; when it is less than 500 mg, the content of the first conductive organic monomer increases relatively, thereby causing self-polymerization, so that some of the first conductive organic monomers cannot be attached to the worm-like porous graphite wire for polymerization; when it is greater than 700 mg, all of the worm-like porous graphite wires cannot be effectively modified (some of the worm-like porous graphite wires cannot be modified), both too low and too high situations will result in the modified porous graphite wire being used as a raw material for further electroplating to have poor conductivity of the porous conductive network.

[0066] In some embodiments, the first template includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetyltrimethylammonium sulfate, etc., preferably cetyltrimethylammonium bromide.

[0067] In some embodiments, the first acidic solution and the second acidic solution both include at least one of hydrochloric acid, hydrofluoric acid, nitric acid, etc. As an optional example, the first acidic solution and the second acidic solution are both 0.3M HCl solutions.

[0068] In some embodiments, the temperature after the first cooling is close to (-4)-2°C, including but not limited to -4°C, -3°C, -2°C, -1°C, 0°C, 1°C or 2°C, etc. As an optional example, the first cooling can be achieved by an ice water bath.

[0069] In some embodiments, the first accelerator includes but is not limited to at least one of ammonium persulfate, potassium persulfate, benzoyl peroxide, etc., preferably ammonium persulfate.

[0070] In some embodiments, the weight ratio of the first promoter to the worm-like porous graphite wire is 1260:500-700, including but not limited to 1260:500, 1260:550, 1260:600, 1260:650 or 1260:700, etc.

[0071] In some embodiments, the temperature of the first polymerization reaction is (-4)-2°C, and the time of the first polymerization reaction is 10-14h. As a non-limiting example, the temperature of the first polymerization reaction includes but is not limited to -4°C, -3°C, -2°C, -1°C, 0°C, 1°C or 2°C, etc., and can be achieved by an ice water bath, etc.; the time of the first polymerization reaction includes but is not limited to 10h, 11h, 12h, 13h or 14h, etc.

[0072] In some embodiments, when solution A and solution B are subjected to a first polymerization reaction, solution B needs to be added to solution A dropwise.

[0073] In some embodiments, after the first polymerization reaction of solution A and solution B, the product of the first polymerization reaction needs to be washed with deionized water and dried in sequence.

[0074] In some embodiments, the first dispersed dispersant includes, but is not limited to, at least one of ethanol, deionized water, methanol, and the like.

[0075] In some embodiments, the concentration of the product of the first dispersed dispersion in which the expandable graphite is modified by the first conductive organic monomer (i.e., the worm-like porous graphite wire modified by the linear polymerization of the first conductive organic monomer) is 10-20 mg / ml, including but not limited to 10 mg / ml, 12 mg / ml, 15 mg / ml, 18 mg / ml or 20 mg / ml, etc.

[0076] In some embodiments, both the first dispersion and the third dispersion are ultrasonic dispersions, and the frequency of the ultrasonic treatment is 10-15KHz, including but not limited to 10KHz, 12.5KHz or 15KHz, etc. Optionally, the time of the first dispersion is 0.5-1h, including but not limited to 0.5h, 0.7h or 1h, etc. Optionally, the time of the third dispersion is 1.5-3h, including but not limited to 1.5h, 2h or 3h, etc.

[0077] S102, using colloidal liquid as electrolyte to electroplate the porous template, and then etching away the porous template to obtain a conductive network.

[0078] In some embodiments, the porous template includes but is not limited to at least one of nickel foam, copper foam, melamine foam, and aluminum foam, preferably nickel foam.

[0079] In some embodiments, the process conditions of electroplating include: the negative electrode is a porous template, the positive electrode is ITO-coated conductive glass, the distance between the negative electrode and the positive electrode is 0.5-1.5 cm, the applied voltage is 40-60 V, and the electroplating time is 15-25 min. As a non-limiting example, the distance between the negative electrode and the positive electrode includes but is not limited to 0.5 cm, 0.1 cm or 1.5 cm, the applied voltage includes but is not limited to 40 V, 50 V or 60 V, and the electroplating time includes but is not limited to 15 min, 20 min or 25 min.

[0080] In some embodiments, during the process of etching away the porous template, the etchant is a ferric chloride solution, including but not limited to a 3M ferric chloride solution; the etching time is 20-28 hours, including but not limited to 20 hours, 22 hours, 24 hours, 26 hours or 28 hours, etc.

[0081] In some embodiments, the method for preparing the anti-icing coating further includes the steps of sequentially performing ultrasonic cleaning and plasma cleaning on the porous template before electroplating the porous template.

[0082] It should be noted that cleaning with a plasma cleaning machine can improve the hydrophilicity of the porous template and further improve its binding force with the worm-like porous graphite wire modified by the linearly polymerized first conductive organic monomer.

[0083] Optionally, the porous template is ultrasonically cleaned with 0.2 M HCl solution, anhydrous ethanol and acetone in sequence, and the ultrasonic cleaning time of each of the 0.2 M HCl solution, anhydrous ethanol and acetone is 10 min.

[0084] Optionally, the method of using a plasma cleaning agent to clean the porous template after ultrasonic cleaning is: the porous template after ultrasonic cleaning is cleaned in an oxygen-injected plasma cleaning agent at a power of 50-100W for 10 minutes.

[0085] S103, modifying the expandable microspheres with a second conductive organic monomer, and then performing a second dispersion in a high-temperature curing resin to obtain a dispersion.

[0086] In some embodiments, the second conductive organic monomer includes but is not limited to at least one of pyrrole, aniline, phenylacetylene, etc., preferably pyrrole. It should be noted that in the embodiments of the present application, the second conductive organic monomer and the first conductive organic monomer may be the same or different, but preferably the same.

[0087] In some embodiments, the expandable microspheres are of a core-shell structure, the core is a hydrocarbon, and the shell is an acrylonitrile copolymer. It is understood that the expandable microspheres begin to expand and / or foam when heated to a temperature above about the initial expansion temperature (the shell softens, the alkane inside the shell gasifies and expands, and the volume of the microspheres increases by dozens or hundreds of times, thereby achieving a foaming effect.), and they begin to shrink at the maximum expansion (contraction) temperature.

[0088] As an optional example, the expandable microspheres are expandable microspheres of model U80 produced by Foshan Jusheng Chemical Co., Ltd., with an average particle size of 10-20 μm, an expansion starting temperature of 100-110° C., and a maximum expansion (contraction) temperature of 140-150° C.

[0089] In some embodiments, the method of modifying expandable microspheres with a second conductive organic monomer comprises:

[0090] 1) dispersing the expandable microspheres in a third acidic solution containing a second template, then performing a second cooling, and adding a second conductive organic monomer to obtain a solution C;

[0091] 2) adding the second accelerator to the fourth acidic solution to obtain solution D;

[0092] 3) subjecting solution C and solution D to a second polymerization reaction to obtain expandable microspheres modified by a linearly polymerized second conductive organic monomer.

[0093] It should be noted that in the method of modifying expandable microspheres with the second conductive organic monomer, the order of step 1) and step 2) can be interchanged.

[0094] In some embodiments, the content of the second template in the fourth dispersed dispersion (the third acidic solution containing the second template) is 0.3-1 wt.%, including but not limited to 0.3 wt%, 0.5 wt%, 0.8 wt% or 1 wt%.

[0095] In some embodiments, the mass ratio of the expandable microspheres to the second template is (500-700):33, including but not limited to 500:33, 550:33, 600:33, 650:33 or 700:33, etc.

[0096] In some embodiments, the amount of expandable microspheres and the second conductive organic monomer is in the following relationship: 500-700 mg of expandable microspheres per 100 μl of the second conductive organic monomer. As non-limiting examples, the amount of expandable microspheres per 100 μl of the second conductive organic monomer includes but is not limited to 500 mg, 550 mg, 600 mg, 650 mg or 700 mg.

[0097] In some embodiments, the second template includes at least one of cetyltrimethylammonium bromide, cetyltrimethylammonium chloride, cetyltrimethylammonium sulfate, etc., preferably cetyltrimethylammonium bromide.

[0098] In some embodiments, the third acidic solution and the fourth acidic solution both include at least one of hydrochloric acid, hydrofluoric acid, nitric acid, etc. As an optional example, the first acidic solution and the second acidic solution are both 0.3M HCl solutions.

[0099] In some embodiments, the temperature after the second cooling is close to (-4)-2°C, including but not limited to -4°C, -3°C, -2°C, -1°C, 0°C, 1°C or 2°C, etc. As an optional example, the first cooling can be achieved by an ice water bath.

[0100] In some embodiments, the second accelerator includes but is not limited to at least one of ammonium persulfate, potassium persulfate, benzoyl peroxide, etc., preferably ammonium persulfate.

[0101] In some embodiments, the weight ratio of the second promoter to the expandable microspheres is 1260:500-700, including but not limited to 1260:500, 1260:550, 1260:600, 1260:650 or 1260:700, etc.

[0102] In some embodiments, the temperature of the second polymerization reaction is (-4)-2°C, and the time of the second polymerization reaction is 10-14h. As a non-limiting example, the temperature of the second polymerization reaction includes but is not limited to -4°C, -3°C, -2°C, -1°C, 0°C, 1°C or 2°C, etc., and can be achieved by an ice water bath, etc.; the time of the second polymerization reaction is but is not limited to 10h, 11h, 12h, 13h or 14h, etc.

[0103] In some embodiments, when solution C and solution D are subjected to a second polymerization reaction, solution D needs to be added to solution C dropwise.

[0104] In some embodiments, after the second polymerization reaction of solution C and solution D, the product of the second polymerization reaction needs to be washed with deionized water and dried in sequence.

[0105] In some embodiments, the high temperature curing resin includes but is not limited to at least one of polydimethylsiloxane (PDMS), amorphous fluoropolymer, AF1601, polytetrafluoroethylene (PTFE), polychlorotrifluoroethylene (PCTFE), etc., preferably polydimethylsiloxane (PDMS). As an optional example, the high temperature curing resin is SYLGARDTM184 polydimethylsiloxane resin and its curing agent produced by Dow Corning Corporation of the United States.

[0106] In some embodiments, when the high temperature curing resin is AF1601 or the like, the high temperature curing resin does not need to be diluted.

[0107] In other embodiments, when the high temperature curing resin is selected from at least one of polydimethylsiloxane, amorphous fluoropolymer, polytetrafluoroethylene, polytrifluorochloroethylene, etc., the second dispersion is carried out in the diluted high temperature curing resin, and the diluent includes but is not limited to at least one of tetrahydrofuran, toluene, dichloromethane, n-hexane, perfluoro (2-butenyltetrahydrofuran), perfluoro (tributylamine), perfluorohexane, perfluorooctylethylene, perfluorooctane, etc. Optionally, when the high temperature curing resin is at least one of polydimethylsiloxane, polytetrafluoroethylene, polytrifluorochloroethylene, the diluent can be selected from tetrahydrofuran, toluene, dichloromethane, ethyl acetate, etc.; and when the high temperature curing resin is an amorphous fluoropolymer, the diluent can be selected from perfluoro (2-butenyltetrahydrofuran), perfluoro (tributylamine), perfluorohexane, perfluorooctylethylene, perfluorooctane, FC-40 fluorinated liquid (3MTM FluorinertTM electronic fluorinated liquid), etc. It is understandable that the high temperature curing resin diluted with the diluent can be directly selected from commercial products, such as Teflon™ AF series, such as Teflon™ AF1601, Teflon™ AF2400, etc.

[0108] In some embodiments, the content of the product of the expandable microspheres modified by the second conductive organic monomer in the second dispersed dispersion (i.e., the expandable microspheres modified by the linearly polymerized second conductive organic monomer) is 4-5wt%, including but not limited to 4wt%, 4.2wt%, 4.5wt%, 4.8wt% or 5wt%, etc.

[0109] In some embodiments, the mass ratio of the high temperature curing resin to the expandable microspheres modified with the second conductive organic monomer is 10:0.8-10:1, including but not limited to 10:0.8, 10:0.85, 10:0.9, 10:0.95 or 10:1.

[0110] In some embodiments, the second dispersion and the fourth dispersion are both ultrasonically dispersed. Optionally, the frequency of the second dispersion ultrasonic treatment is 20-30KHz, including but not limited to 20KHz, 22KHz, 25KHz, 28KHz or 30KHz, etc.; the time of the second dispersion is 6-8h, including but not limited to 6h, 7h or 8h, etc. Optionally, the frequency of the fourth dispersion ultrasonic treatment is 10-15KHz, including but not limited to 10KHz, 12.5KHz or 15KHz, etc.; the time of the fourth dispersion is 1.5-3h, including but not limited to 1.5h, 2h or 3h, etc.

[0111] S104, placing the conductive network obtained in step S102 on the surface of the substrate, and distributing the dispersion obtained in step S103 on the conductive grid and the substrate, followed by heating for expansion, heating for contraction, and cooling in sequence to obtain a three-dimensional porous coating.

[0112] In some embodiments, the substrate is selected from at least one of a metal material, a non-metal material, an inorganic material, an organic material or a composite material. As a non-limiting example, the substrate includes but is not limited to an Al sheet, a GCr15 steel sheet, a silicon sheet, a glass fiber reinforced plastic, and other materials that can be subjected to surface sandblasting. Preferably, the substrate is a glass fiber reinforced plastic sheet.

[0113] In some embodiments, the method for preparing the anti-icing coating further includes the step of sandblasting or acid etching the surface of the substrate before placing the conductive network obtained in step S102 on the surface of the substrate. Sandblasting or acid etching the surface of the substrate can ensure that the surface of the substrate achieves a relatively uniform roughness level of about 10-30 μm. As a non-limiting example, the roughness of the substrate surface includes but is not limited to 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc.

[0114] In some embodiments, the method for distributing the dispersion obtained in step S103 on the conductive grid and the substrate is: dropping the dispersion obtained in step S103 onto the surface of the conductive network agent substrate to allow it to naturally level, and then placing the substrate, conductive network, and dispersion in a vacuum dryer and evacuating to -0.1 MPa, so that the dispersion can fill the pores of the conductive network as much as possible.

[0115] In some embodiments, the amount of the dispersion obtained in step S103 distributed on the conductive grid and the substrate is: 200-250 μl of the dispersion obtained in step S103 is used per square centimeter of the conductive network. As a non-limiting example, the amount of the dispersion obtained in step S103 used per square centimeter of the conductive network is 200 μl, 210 μl, 220 μl, 230 μl, 240 μl or 250 μl, etc.

[0116] In some embodiments, the temperature of heating and expansion is set according to the expansion temperature of the expandable microspheres modified by the linearly polymerized second conductive organic monomer (also the expansion starting temperature of the expandable microspheres), so that the expandable microspheres modified by the linearly polymerized second conductive organic monomer (that is, the product after the expandable microspheres are modified by the second conductive organic monomer) expand, and the conductive network and matrix composite containing the dispersion obtained in step S103 are kept at the heating and expansion temperature for a period of time to ensure that the high-temperature curable resin is cured. Optionally, the temperature of heating and expansion is 100-130°C, and the time of heating and expansion is 3-6h. As a non-limiting example, the temperature of heating and expansion includes but is not limited to 100°C, 105°C, 110°C, 115°C, 120°C, 125°C or 130°C, etc., and the time of heating and expansion includes but is not limited to 3h, 4h, 5h or 6h, etc.

[0117] In some embodiments, the method for preparing the anti-icing coating further includes the step of preheating the conductive grid and substrate distributed with the dispersion before heating and expansion. Preheating the conductive grid and substrate distributed with the dispersion before heating and expansion can provide a buffer period for heating and expansion, so that the high-temperature curing resin can be pre-cured and formed, thereby avoiding the problem of poor performance of the anti-icing coating caused by the temperature change caused by the high temperature of direct heating and expansion. Therefore, the preheating temperature needs to be lower than the heating and expansion temperature. As a non-limiting example, the preheating temperature is 80-90°C, including but not limited to 80°C, 82°C, 85°C, 88°C or 90°C, etc.

[0118] In some embodiments, the temperature of heating and shrinking is set according to the shrinkage temperature of the expandable microspheres modified by the linearly polymerized second conductive organic monomer (also the maximum expansion (contraction) temperature of the expandable microspheres), so that the expandable microspheres modified by the linearly polymerized second conductive organic monomer (that is, the product after the expandable microspheres are modified by the second conductive organic monomer) shrink to at least the original size or break. At this time, since the surrounding high-temperature curing resin has been cured, three-dimensional holes and pores are generated, and after cooling, a three-dimensional porous coating obtained by robust curing can be achieved. Optionally, the temperature of heating and shrinking is 140-160°C, including but not limited to 140°C, 145°C, 150°C, 155°C, or 160°C, etc.

[0119] It should be noted that in the embodiments of the present application, the time of heating and shrinking is not limited, as long as the expandable microspheres modified by the linearly polymerized second conductive organic monomer can be shrunk to at least the original size or ruptured.

[0120] In some embodiments, the cooling method includes but is not limited to air cooling, etc. Optionally, when air cooling is used, the cooling time is 8-12 hours, including but not limited to 8 hours, 9 hours, 10 hours, 11 hours or 12 hours, etc.

[0121] S105, distributing the oily liquid on the surface and inner pores of the three-dimensional porous coating to obtain an anti-icing coating.

[0122] In some embodiments, the method for preparing the anti-icing coating further includes a step of surface treating the three-dimensional porous coating before distributing the oily liquid on the surface and inside of the three-dimensional porous coating. Optionally, the surface treatment includes polishing the three-dimensional porous coating to remove the surface cured resin and expose the internal pores.

[0123] In some embodiments, the oily liquid includes but is not limited to at least one of silicone oil and perfluoropolyether oil. Optionally, the silicone oil includes but is not limited to at least one of dimethyl silicone oil, phenyl silicone oil, amino silicone oil, etc.

[0124] It should be noted that in the embodiments of the present application, in order to improve the affinity between the oil-based liquid and the porous coating, further improve the preservation and storage time of the oil-based liquid in the porous layer, and enhance the robustness of the low ice adhesion characteristics of the three-dimensional porous coating, the oily liquid is selected to be an oil with the same properties and high affinity as the high-temperature curing resin. For example, when the high-temperature curing resin is polydimethylsiloxane, the oily liquid is dimethyl silicone oil; when the high-temperature curing resin is at least one of polytetrafluoroethylene, polytrifluorochloroethylene, and amorphous fluorinated polymers, the oily liquid is selected to be perfluoropolyether oil.

[0125] In some embodiments, the method of distributing the oily liquid on the surface of the three-dimensional porous coating is: uniformly dropping the oily liquid on the surface of the three-dimensional porous coating, and then vacuum dipping to make it (the oily liquid dropped on the surface of the three-dimensional porous coating) fully infiltrate the surface and internal pores of the three-dimensional porous coating. Optionally, the vacuum dipping time is 20-40 minutes, including but not limited to 20 minutes, 25 minutes, 30 minutes, 35 minutes or 40 minutes.

[0126] In some embodiments, the method for preparing the anti-icing coating further includes the step of distributing the oily liquid on the surface and inside of the three-dimensional porous coating and then removing excess oily liquid on the outer layer of the surface of the three-dimensional porous coating.

[0127] As an optional example, the method for removing excess oily liquid on the surface of the three-dimensional porous coating is: placing the three-dimensional porous coating sample with oily liquid distributed thereon at 90° vertically for 10 hours to allow excess oil on the outer layer of the three-dimensional porous coating surface to drain.

[0128] In the embodiments of the present application, the principles of modifying the worm-like porous graphite wire by linear polymerization of the first conductive organic monomer and modifying the expandable microsphere by linear polymerization of the second conductive organic monomer are basically the same. Taking the second conductive organic monomer as pyrrole and the linear polypyrrole modified expandable microsphere as an example, the principle of modifying the expandable microsphere by linear polymerization of the second conductive organic monomer is: the second conductive organic monomer first bonds with the expandable microsphere, and then during the reaction process, the free second organic monomer gradually undergoes polymerization reaction with the already bonded second organic monomer to produce a polypyrrole chain, and finally forms a linear polypyrrole modified expandable microsphere, thereby achieving conductive properties.

[0129] As an optional example, the anti-icing coating of the embodiment of the present application includes the following steps:

[0130] (1) The substrate is subjected to surface sandblasting or acid etching to ensure that the surface of the substrate has a relatively uniform roughness level of about 10-30 μm;

[0131] (2) Expandable graphite (flake graphite, size 75 μm) at 300-400°C to form worm-like porous graphite wire;

[0132] (3) Add 33 mg of hexadecyltrimethylammonium bromide (CTAB) to 10 ml of 0.3 M HCl solution and stir to dissolve for 10 min; add 500-700 mg of worm-like porous graphite wire to the above solution and ultrasonicate for 2 h to make it evenly dispersed, and the frequency of ultrasonic treatment is 10-15 kHz; place the sonicated solution in an ice water bath for 5 min to make its temperature close to (-2)-0°C, add 100 μl of pyrrole (Py) monomer to the above solution and stir for 30 min to mix it evenly to obtain solution A; further add 1.26 g of ammonium persulfate to 0.3 M HCl solution to prepare solution B; add solution B dropwise to solution A, and place the whole (solution A with solution B added) in an ice water bath for 12 h for polymerization reaction; the obtained black powder is centrifuged and washed with deionized water for 3 times; and dried at 80°C in vacuum for 24 h to obtain linear Ppy-modified worm-like porous graphite wire, named L-Ppy-EG;

[0133] (4) dispersing the linear polypyrrole-modified worm-like porous graphite wire L-Ppy-EG in ethanol (at a concentration of 10-20 mg / ml), and ultrasonicating for 0.5-1 h to uniformly disperse it into a colloidal liquid, with the frequency of ultrasonic treatment being 10-15 kHz;

[0134] (5) using 0.2M HCl solution, anhydrous ethanol, and acetone to ultrasonically clean the nickel foam (1cm*1cm*1.5mm) for 10 minutes, and then cleaning the cleaned nickel foam in an oxygen injection plasma cleaning machine for 10 minutes (power of 50-100W) to enhance the hydrophilicity of the nickel foam and further improve its binding force with L-Ppy-EG;

[0135] (6) electroplating the nickel foam after cleaning as the negative electrode, the ITO-coated conductive glass as the positive electrode, and the L-Ppy-EG colloidal solution dispersed in ethanol as the electrolyte, with the distance between the two electrodes being 1 cm, the applied voltage being 50 V, and the electroplating being performed for 20 min so that the graphite wire in the colloidal solution is plated onto the nickel foam, and further drying the electroplated nickel foam in a vacuum drying oven at 80° C. for 1 h;

[0136] (7) A 3 M FeCl 3 solution was prepared, and the dried electroplated worm-like porous graphite wire foam nickel sample was immersed in the solution for 24 h to etch and remove the internal foam nickel, thereby obtaining a polypyrrole-modified graphite wire conductive network.

[0137] (8) using the method in step (3) to modify the expandable microspheres (particle size of 10-30 μm) with linear polypyrrole to prepare linear polypyrrole-modified expandable microspheres, named L-Ppy-EM;

[0138] (9) adding L-Ppy-EM to the diluted high temperature curable resin (the diluent can be tetrahydrofuran, toluene, dichloromethane, n-hexane, etc.), adjusting the mass fraction of L-Ppy-EM in the high temperature curable resin to be in the range of 8-10wt.% (L-Ppy-EM accounts for 4-5% of the total mass of the high temperature curable resin plus the diluent), and ultrasonicating for 6-8h to make it evenly dispersed into a colloidal liquid, and the frequency of ultrasonic treatment is 20-30kHz;

[0139] (10) placing the polypyrrole-modified graphite wire conductive network prepared in step (7) on the surface of the substrate treated in step (1), dripping an appropriate amount of the dispersion obtained in step (9) onto the conductive network and the surface of the substrate to allow it to flow naturally, placing the substrate, the conductive network, and the dispersion in a vacuum dryer and evacuating the temperature to -0.1 MPa so that the dispersion fills the pores of the conductive network as much as possible.

[0140] (11) The conductive network-matrix composite containing the dispersion obtained in step (10) is preheated at 80-90°C to cure the high-temperature curing resin, and then a suitable temperature (100-130°C) is set according to the expansion temperature of the selected L-Ppy-EM to make it expand. This state is maintained for 3h-6h, and then the temperature is set to 140-160°C to allow the L-Ppy-EM to fully shrink (shrink to the original size or even smaller or break), thereby generating three-dimensional holes and voids. Air cooling for 10h is performed to achieve robust curing to obtain a three-dimensional porous coating, and the surface is simply polished with sandpaper to expose the internal holes.

[0141] (12) An oily liquid with the same properties and high affinity as the high-temperature curing resin is evenly dropped onto the surface of the three-dimensional porous coating and vacuum dip-coated for 30 min to fully wet the coating surface and inner pores. The sample is then placed vertically at 90° for 10 h to allow excess oil on the outer layer of the coating surface to drain, thereby obtaining a three-dimensional porous oil-injected anti-icing coating with high affinity for the selected oil.

[0142] The preparation method of the anti-icing coating in the embodiment of the present application is based on the synergistic coupling of a conductive network prepared from expandable graphite modified by a linear poly first conductive organic monomer and expandable microspheres modified by a linear poly second conductive organic monomer, so as to obtain a three-dimensional porous oleophilic anti-icing coating with excellent photothermal and electrothermal properties. The method mainly combines active and passive modes, namely, the photothermal conversion of expandable microspheres modified with linear poly second conductive organic monomers having photothermal effect, the electrothermal effect of expandable graphite modified with linear poly first conductive organic monomers to form a conductive network, and the low ice adhesion characteristics caused by the porous lipophilicity of the coating itself. The preparation can be realized on the surface of common substrates (such as Al, GCr15, stainless steel, fiberglass, etc.). The electrothermal and photothermal effects can be achieved by regulating the temperature change of the surface (for the coating, the temperature will rise when electricity is added (it will cool down when the electricity is removed), and the light will also increase its temperature, and it will cool down when the light is removed). Combined with the oil film generated in the preparation process of the coating itself, the ice adhesion strength of the surface can be greatly reduced (for example, it can be reduced by more than 96% compared with ordinary fiberglass sheets) and the freezing time can be delayed. At the same time, due to the high affinity of the three-dimensional porous structure and the high temperature curing resin itself to the selected oil, the oil can be stored for a long time, which greatly improves the robustness of the low ice adhesion performance of the coating.

[0143] The anti-icing coating of the embodiment of the present application is prepared by the anti-icing coating preparation method of the embodiment of the present application.

[0144] The anti-icing coating of the embodiment of the present application can be widely used in the fields of electricity, transportation, communications or aviation, including but not limited to heat exchanger frost protection, wind turbine blade frost protection, vehicle frost protection, ship frost protection, aircraft surface frost protection or power and communication facilities frost protection.

[0145] Certain features of the present technology are further illustrated in the following non-limiting examples.

[0146] 1. Examples and Comparative Examples

[0147] Example 1

[0148] The method for preparing the anti-icing coating of this embodiment comprises the following steps:

[0149] (1) The substrate material is a glass fiber reinforced plastic sample with a size of 1.5 cm*1.5 cm*1 mm. Sandblasting is used to achieve a surface roughness of about 30 um to obtain a sandblasted glass fiber reinforced plastic sample.

[0150] (2) Expandable graphite (flake graphite, size 75 μm) is expanded at 400°C for 5 h to form worm-like porous graphite wires.

[0151] (3) 33 mg of hexadecyltrimethylammonium bromide (CTAB) was added to 10 mL of 0.3 M HCl solution and stirred for 10 min to dissolve; 600 mg of worm-like porous graphite was added to the above solution and ultrasonicated for 2 h to make it evenly dispersed, and the frequency of ultrasonic treatment was 12 kHz; the sonicated solution was placed in an ice-water bath for 5 min to make its temperature close to (-2)-0°C, 100 μl of pyrrole (Py) monomer was added to the above solution and stirred for 30 min to make it evenly mixed to obtain solution A; 1.26 g of ammonium persulfate was further added to 20 mL of 0.3 M HCl solution to prepare solution B; solution B was added dropwise to solution A, and the whole (solution A with solution B added) was placed in an ice-water bath for 12 h for polymerization reaction; the obtained black powder was centrifuged and washed with deionized water three times; and vacuum dried at 80°C for 24 h to obtain linear Ppy-modified worm-like porous graphite (500 mg), named L-Ppy-EG.

[0152] (4) dispersing the linear polypyrrole-modified worm-like porous graphite wire L-Ppy-EG obtained in step (3) in ethanol (at a concentration of 15 mg / ml), and ultrasonicating for 0.8 h to uniformly disperse it into a colloidal liquid, with the frequency of ultrasonic treatment being 12 kHz;

[0153] (5) The nickel foam (1 cm*1 cm*1.5 mm) was ultrasonically cleaned for 10 min using 0.2 M HCl solution, anhydrous ethanol, and acetone, respectively. The cleaned nickel foam was then cleaned in an oxygen-injected plasma cleaning machine for 10 min (power of 80 W) to enhance the hydrophilicity of the nickel foam and further improve its binding force with L-Ppy-EG.

[0154] (6) The nickel foam cleaned in step (5) is used as the negative electrode, the ITO-coated conductive glass is used as the positive electrode, and the L-Ppy-EG colloidal solution dispersed in ethanol in step (4) is used as the electrolyte to electroplate the nickel foam. The distance between the two electrodes is 1 cm, the applied voltage is 50 V, and the electroplating is performed for 20 minutes so that the graphite wire in the colloidal solution is plated on the nickel foam. The electroplated nickel foam is further dried in a vacuum drying oven at 80° C. for 1 hour to obtain a nickel foam sample with electroplated worm-like porous graphite wires.

[0155] (7) preparing a 3M FeCl3 solution, and immersing the dried electroplated worm-like porous graphite wire foam nickel sample obtained in step (6) therein for 24 hours to etch and remove the internal foam nickel, thereby obtaining a linear polypyrrole-modified graphite wire conductive network.

[0156] (8) Using the method in step (3) to modify the expandable microspheres with linear polypyrrole, the specific method is as follows:

[0157] 33 mg of hexadecyltrimethylammonium bromide (CTAB) was added to 10 mL of 0.3 M HCl solution, and stirred for 10 min to dissolve; 300 mg of expandable microspheres were added to the above solution, and ultrasonicated for 2 h to make them dispersed evenly, and the frequency of ultrasonication was 12 kHz; the ultrasonicated solution was placed in an ice water bath for 5 min to make its temperature close to (-2)-0°C, 100 μl of pyrrole (Py) monomer was added to the above solution, and stirred for 30 min to make it mixed evenly to obtain solution C; the over- 1.26 g of ammonium sulfate was added to 10 mL of 0.3 M HCl solution to prepare solution D; solution D was added dropwise into solution C, and the whole (solution C with solution D added) was placed in an ice-water bath for 12 h for polymerization reaction; the obtained black powder was washed three times by centrifugation with deionized water; and dried at 80 ° C in vacuum for 24 h to obtain usable linear polypyrrole-modified expandable microspheres (60 mg), named L-Ppy-EM, and the rest were invalid microspheres that were damaged during the modification process and could not perform the expansion and contraction functions.

[0158] The expandable microspheres are U80 expandable microspheres produced by Foshan Jusheng Chemical Co., Ltd., with an average particle size of 10-20 μm, an expansion starting temperature of 100-110° C., and a maximum expansion (contraction) temperature of 140-150° C.

[0159] (9) The L-Ppy-EM obtained in step (8) was added to the PDMS (polydimethylsiloxane) resin diluted with toluene (toluene: PDMS: curing agent = 0.5 ml: 1 ml: 0.1 ml), and the mass fraction of L-Ppy-EM was adjusted to 9 wt %, and it was evenly dispersed by ultrasound at a frequency of 25 kHz for 6 h, and then vacuum degassed for 1 h to obtain a dispersion.

[0160] The PDMS resin can be purchased from Dow Corning Corporation of the United States, and the model used is SYLGARDTM184 polydimethylsiloxane resin and its curing agent.

[0161] (10) The linear polypyrrole modified graphite wire conductive network with a size of 1.5 cm*1.5 cm*1 mm (the size of the nickel foam used as a template and etched away is 1.5 cm*1.5 cm*1 mm) prepared in step (7) is placed on the upper surface of the sandblasted glass fiber reinforced plastic sample obtained in step (1), and then 500 μl of the dispersion obtained in step (9) is dripped on the linear polypyrrole modified graphite wire conductive network obtained in step (7) and the sandblasted glass fiber reinforced plastic sample obtained in step (1) to allow it to flow naturally. The sandblasted glass fiber reinforced plastic sample, the linear polypyrrole modified graphite wire conductive network, and the dispersion are placed in a vacuum drying pot and infiltrated at -0.1 MPa for 30 minutes to allow the dispersion to completely enter the porous (i.e., pores) of the polypyrrole modified graphite wire conductive network, thereby obtaining a conductive network-matrix complex containing the dispersion.

[0162] (11) The conductive network-matrix complex containing the dispersion obtained in step (10) is heated at 85°C for 30 minutes to solidify the PDMS (polydimethylsiloxane) resin, then heated to 110°C to allow the L-Ppy-EM to begin to expand and maintain this state for 3 hours, and finally maintained at 150°C for 5 hours to allow the L-Ppy-EM to fully shrink (to the original size or even smaller or broken) to form an internal three-dimensional pore structure, and finally air-cooled for 12 hours to obtain a three-dimensional porous coating, and after a simple sandpaper polishing to remove the surface solidified resin, a conductive three-dimensional porous oleophilic structure coating is obtained.

[0163] (12) 0.5 mL of oily liquid dimethyl silicone oil (purchased from Sigma Aldrich, viscosity 100±8 mPa·s) was evenly dropped on the surface of the three-dimensional porous coating finally obtained in step (11), and vacuum was drawn in a vacuum dryer for 30 min to fully wet the coating. The sample was then placed vertically at 90° for 10 h to allow the excess oil on the outer layer of the coating surface to drain, thereby obtaining a three-dimensional porous oil-injected anti-icing coating with a high affinity for the silicone oil of this embodiment.

[0164] Figure 2 This is a comparison diagram of the expandable graphite expanding into a worm-like graphite line in step (2) of this embodiment. Figure 2 It can be seen that linear worm-like graphite was successfully prepared, laying the foundation for the subsequent preparation of conductive porous networks.

[0165] Figure 3This is a physical picture of the linear Ppy-modified worm-like porous graphite wire L-Ppy-EG obtained in step (3) of this embodiment, which further modifies the conductivity of the worm-like porous graphite wire obtained in step (2).

[0166] Figure 4 The following are the physical comparison pictures of the linear polypyrrole modified graphite wire conductive network obtained in step (7) of this embodiment at different angles. Figure 4 It can be seen that the conductive network has a certain mechanical strength, can be bent and deformed to a certain extent, and the porous pores inside are also clearly visible.

[0167] Figure 6 The following are the actual linear polypyrrole-modified expandable microspheres L-Ppy-EM obtained in step (8) of this embodiment and the scanning electron microscope test images at different scales. Figure 6 It can be seen that the expandable microspheres turn black after being modified with linear polypyrrole, and the spherical expandable microspheres are modified with linear polypyrrole molecules, which further increases the contact between particles and enhances the conductivity of the coating.

[0168] Figure 7 The actual image and cross-sectional porous image of the conductive three-dimensional porous coating finally obtained in step (11) of this embodiment. Figure 7 It can be seen that the cross-section of the coating is a three-dimensional porous morphology, which is conducive to the storage of the affinity oil with the coating.

[0169] Example 2

[0170] The method for preparing the anti-icing coating of this embodiment comprises the following steps:

[0171] (1) The substrate material is an aluminum sheet sample with a size of 1.5 cm*1.5 cm*1 mm, and an acid etching treatment is used to achieve a surface roughness of about 10 um to obtain an acid-etched aluminum sheet sample.

[0172] (2) Expandable graphite (flake graphite, size 75 μm) is expanded at 400°C for 5 h to form worm-like porous graphite wires.

[0173] (3) 33 mg of hexadecyltrimethylammonium bromide (CTAB) was added to 10 mL of 0.3 M HCl solution and stirred for 10 min to dissolve; 600 mg of worm-like porous graphite was added to the above solution and ultrasonicated for 2 h to make it evenly dispersed, and the frequency of ultrasonic treatment was 12 kHz; the sonicated solution was placed in an ice-water bath for 5 min to make its temperature close to (-2)-0°C, 100 μl of pyrrole (Py) monomer was added to the above solution and stirred for 30 min to make it evenly mixed to obtain solution A; 1.26 g of ammonium persulfate was further added to 20 mL of 0.3 M HCl solution to prepare solution B; solution B was added dropwise to solution A, and the whole (solution A with solution B added) was placed in an ice-water bath for 12 h for polymerization reaction; the obtained black powder was centrifuged and washed with deionized water three times; and vacuum dried at 80°C for 24 h to obtain linear Ppy-modified worm-like porous graphite (500 mg), named L-Ppy-EG.

[0174] (4) dispersing the linear polypyrrole-modified worm-like porous graphite wire L-Ppy-EG obtained in step (3) in ethanol (at a concentration of 15 mg / ml), and ultrasonicating for 0.8 h to uniformly disperse it into a colloidal liquid, with the frequency of ultrasonic treatment being 12 kHz;

[0175] (5) The nickel foam (1 cm*1 cm*1.5 mm) was ultrasonically cleaned for 10 min using 0.2 M HCl solution, anhydrous ethanol, and acetone, respectively. The cleaned nickel foam was then cleaned in an oxygen-injected plasma cleaning machine for 10 min (power of 80 W) to enhance the hydrophilicity of the nickel foam and further improve its binding force with L-Ppy-EG.

[0176] (6) The nickel foam cleaned in step (5) is used as the negative electrode, the ITO-coated conductive glass is used as the positive electrode, and the L-Ppy-EG colloidal solution dispersed in ethanol in step (4) is used as the electrolyte to electroplate the nickel foam. The distance between the two electrodes is 1 cm, the applied voltage is 50 V, and the electroplating is performed for 20 minutes so that the graphite wire in the colloidal solution is plated on the nickel foam. The electroplated nickel foam is further dried in a vacuum drying oven at 80° C. for 1 hour to obtain a nickel foam sample with electroplated worm-like porous graphite wires.

[0177] (7) preparing a 3M FeCl3 solution, and immersing the dried electroplated worm-like porous graphite wire foam nickel sample obtained in step (6) therein for 24 hours to etch and remove the internal foam nickel, thereby obtaining a linear polypyrrole-modified graphite wire conductive network.

[0178] (8) Using the method in step (3) to modify the expandable microspheres with linear polypyrrole, the specific method is as follows:

[0179] 33 mg of hexadecyltrimethylammonium bromide (CTAB) was added to 10 mL of 0.3 M HCl solution, and stirred for 10 min to dissolve; 300 mg of expandable microspheres were added to the above solution, and ultrasonicated for 2 h to make them dispersed evenly, and the frequency of ultrasonication was 12 kHz; the ultrasonicated solution was placed in an ice water bath for 5 min to make its temperature close to (-2)-0°C, 100 μl of pyrrole (Py) monomer was added to the above solution, and stirred for 30 min to make it mixed evenly to obtain solution C; further 1.26 g of ammonium persulfate was added to 15 mL of 0.3 M HCl solution to prepare solution D; solution D was added dropwise into solution C, and the whole (solution C with solution D added) was placed in an ice-water bath for 12 h for polymerization reaction; the obtained black powder was washed three times with deionized water by centrifugation; and dried at 80 °C in vacuum for 24 h to obtain linear polypyrrole-modified expandable microspheres (60 mg), named L-Ppy-EM, and the rest were invalid microspheres that were damaged during the modification process and could not perform the expansion and contraction functions.

[0180] The expandable microspheres are U80 expandable microspheres produced by Foshan Jusheng Chemical Co., Ltd., with an average particle size of 10-20 μm, an expansion starting temperature of 100-110° C., and a maximum expansion (contraction) temperature of 140-150° C.

[0181] (9) The L-Ppy-EM obtained in step (8) was added to 1 ml of AF1601 resin, the mass fraction of L-Ppy-EM was adjusted to 9 wt%, and the mixture was evenly dispersed by ultrasonic treatment at a frequency of 25 kHz for 6 h, followed by vacuum degassing for 1 h to obtain a dispersion.

[0182] Wherein, AF1601 resin: model TeflonTM AF1601, purchased from Chemours Company, USA.

[0183] (10) The linear polypyrrole modified graphite wire conductive network with a size of 1.5 cm*1.5 cm*1 mm (the size of the nickel foam used as a template and etched away is 1.5 cm*1.5 cm*1 mm) prepared in step (7) is placed on the upper surface of the acid-etched aluminum sheet sample obtained in step (1), and then 500 μl of the dispersion obtained in step (9) is dripped on the linear polypyrrole modified graphite wire conductive network obtained in step (7) and the sandblasted fiberglass sample obtained in step (1) to allow it to flow naturally. The acid-etched aluminum sheet sample, the linear polypyrrole modified graphite wire conductive network, and the dispersion are placed in a vacuum drying pot and infiltrated at -0.1 MPa for 30 min to allow the dispersion to completely enter the porous (i.e., pores) of the polypyrrole modified graphite wire conductive network, thereby obtaining a conductive network-matrix complex containing the dispersion.

[0184] (11) The conductive network-matrix composite containing the dispersion obtained in step (10) is first heated to 90°C to solidify the AF1601 resin, and then further heated to 100°C to allow the L-Ppy-EM to begin to expand and maintain this state for 4.5 hours. Finally, it is maintained at 150°C for 5 hours to allow the L-Ppy-EM to fully shrink (to the original size or even smaller or rupture) to form an internal three-dimensional pore structure. Finally, it is air-cooled for 12 hours to obtain a three-dimensional porous coating. After a simple sandpaper polishing to remove the surface solidified resin, a conductive three-dimensional porous oleophilic structure coating is obtained.

[0185] (12) 0.5 mL of oily liquid perfluoropolyether oil (purchased from Sigma Aldrich, molecular weight Mw-1500) was evenly dropped on the surface of the three-dimensional porous coating finally obtained in step (11), and vacuum was drawn in a vacuum dryer for 30 min to fully wet the coating. The sample was then placed vertically at 90° for 10 h to allow the excess oil on the outer layer of the coating surface to drain, thereby obtaining a three-dimensional porous oil-injected anti-icing coating with a high affinity for the perfluoropolyether oil of this embodiment.

[0186] Example 3

[0187] This embodiment is basically the same as Embodiment 1, except that:

[0188] Replacing the nickel foam in steps (5)-(7) with aluminum foam;

[0189] The electroplating process conditions in step (6) are as follows: the aluminum foam cleaned in step (5) is used as the negative electrode, the ITO-coated conductive glass is used as the positive electrode, and the L-Ppy-EG colloidal solution dispersed in ethanol in step (4) is used as the electrolyte. The distance between the two electrodes is 1 cm, the applied voltage is 20 V, and the electroplating is performed for 20 minutes so that the graphite wire in the colloidal solution is plated onto the aluminum foam. The electroplated aluminum foam is further dried in a vacuum drying oven at 80° C. for 1 hour to obtain a dried aluminum foam sample with electroplated worm-like porous graphite wires.

[0190] Example 4

[0191] This embodiment is basically the same as Embodiment 1, except that:

[0192] In step (3), the amount of worm-like porous graphite wire used is 500 mg, and 410 mg of linear Ppy-modified worm-like porous graphite wire is obtained.

[0193] Example 5

[0194] This embodiment is basically the same as Embodiment 1, except that:

[0195] In step (3), the amount of worm-like porous graphite wire used is 700 mg, and 580 mg of linear Ppy-modified worm-like porous graphite wire is obtained.

[0196] Example 6

[0197] This embodiment is basically the same as Embodiment 1, except that:

[0198] Replacing the pyrrole monomer in step (3) with aniline;

[0199] In step (3), the conditions for the polymerization reaction are as follows: 600 mg of worm-like porous graphite wire is added to 40 ml of hydrochloric acid solution with a concentration of 2 M, and ultrasonicated for 2 hours to make it evenly dispersed, and the frequency of ultrasonic treatment is 12 kHz; the sonicated solution is placed in an ice-water bath and allowed to stand for 5 minutes to make its temperature close to (-2)-0°C, 1 ml of aniline (ANI) monomer is added to the above solution, and stirred for 30 minutes to make it evenly mixed to obtain solution A; further 2 g of ammonium persulfate is added to 20 mL of deionized water to prepare solution B; solution B is added dropwise to solution A (under ice-water bath conditions), and the whole (solution A with solution B added thereto) is placed in an ice-water bath for 12 hours for polymerization reaction; the obtained black powder is centrifuged and washed with deionized water three times; and vacuum dried at 80°C for 24 hours to obtain PANI-modified worm-like porous graphite wire (500 mg), which is named PANI-EG.

[0200] Example 7

[0201] This embodiment is basically the same as Embodiment 1, except that:

[0202] The pyrrole monomers in step (3) and step (8) are replaced by aniline monomers.

[0203] In step (3), the conditions for the polymerization reaction are as follows: 600 mg of worm-like porous graphite wire is added to 40 ml of hydrochloric acid solution with a concentration of 2 M, and ultrasonicated for 2 hours to make it uniformly dispersed, and the frequency of ultrasonic treatment is 12 kHz; the sonicated solution is placed in an ice-water bath and allowed to stand for 5 minutes to make its temperature close to (-2)-0°C, 1 ml of aniline (ANI) monomer is added to the above solution, and stirred for 30 minutes to make it uniformly mixed to obtain solution A; further 2 g of ammonium persulfate is added to 20 mL of deionized water to prepare solution B; solution B is added dropwise to solution A (under ice-water bath conditions), and the whole (solution A with solution B added thereto) is placed in an ice-water bath for 12 hours for polymerization reaction; the obtained black powder is centrifuged and washed with deionized water for 3 times; vacuum dried at 80°C for 24 hours to obtain PANI-modified worm-like porous graphite wire (500 mg), named PANI-EG;

[0204] In step (8), the conditions for the polymerization reaction are as follows: 600 mg of expandable microspheres are added to 40 ml of a 2M hydrochloric acid solution, and ultrasonicated for 2 h to disperse them uniformly, with the frequency of the ultrasonic treatment being 12 kHz; the ultrasonicated solution is placed in an ice-water bath for 5 min to allow its temperature to approach (-2)-0°C, 1 ml of aniline (ANI) monomer is added to the above solution, and stirred for 30 min to mix it uniformly to obtain solution C; further, 2 g of ammonium persulfate is added to 15 mL of a 0.3M HCl solution to prepare solution D; solution D is added dropwise to solution C, and the whole (solution C with solution D added thereto) is placed in an ice-water bath for 12 h for polymerization reaction; the obtained black powder is centrifuged and washed with deionized water three times; and vacuum dried at 80°C for 24 h to obtain usable polyaniline-modified expandable microspheres (80 mg), named PANI-EM, and the rest are invalid microspheres that are damaged during the modification process and thus cannot perform the expansion and contraction functions.

[0205] Example 8

[0206] This embodiment is basically the same as Embodiment 1, except that:

[0207] In step (9), the mass fraction of L-Ppy-EM is 8 wt %.

[0208] Example 9

[0209] This embodiment is basically the same as Embodiment 1, except that:

[0210] In step (9), the mass fraction of L-Ppy-EM is 10 wt %.

[0211] Comparative Example 1

[0212] This comparative example is basically the same as Example 1, except that:

[0213] The expandable microspheres are white microspheres not modified by linear polypyrrole (ie, step (8) is not included). In step (9), the white microspheres not modified by linear polypyrrole are added to the PDMS (polydimethylsiloxane) resin diluted with toluene.

[0214] Comparative Example 2

[0215] This comparative example is basically the same as Example 1, except that:

[0216] The expandable graphite is expandable graphite that is not modified by linear polypyrrole (that is, step (3) is not included), and in step (4), the worm-like porous graphite wire obtained in step (2) is directly dispersed in ethanol.

[0217] Comparative Example 3

[0218] This comparative example is basically the same as Example 1, except that:

[0219] In step (3), the amount of worm-like porous graphite wire used is 450 mg, and 200 mg of worm-like porous graphite wire modified with linear Ppy is obtained.

[0220] Comparative Example 4

[0221] This comparative example is basically the same as Example 1, except that:

[0222] In step (3), the amount of worm-like porous graphite wire used is 750 mg, and 400 mg of worm-like porous graphite wire modified with linear Ppy is obtained.

[0223] Comparative Example 5

[0224] This comparative example is basically the same as Example 1, except that:

[0225] In step (9), the mass fraction of L-Ppy-EM is 6 wt %.

[0226] Comparative Example 6

[0227] This comparative example is basically the same as Example 1, except that:

[0228] In step (9), the mass fraction of L-Ppy-EM is 12 wt %.

[0229] 2. Performance Test

[0230] 1. Test methods

[0231] (1) Electrocaloric effect

[0232] Conductive adhesive was pasted on both sides of the coatings prepared in the embodiment and the comparative example to fix the wires, and voltage was applied to them using an adjustable DC regulated power supply (adjustment range 0-60V, 0-5A). The surface temperature of the samples was measured using a Hikvision infrared thermal imager to test the electrothermal effect of the samples.

[0233] (2) Ice adhesion strength

[0234] Use Fig. 9 The homemade ice adhesion strength testing device shown tests the ice adhesion strength.

[0235] like Fig. 9As shown, the self-made ice adhesion strength test device includes an environment temperature control cabinet 1, an ice column model 3, a stepping push rod 4 and a force sensor. An environment temperature controller is installed on the environment temperature control cabinet 1, and a cooling table 5 is installed at the bottom of the environment temperature control cabinet 1. A cooling table temperature controller for controlling the temperature of the cooling table is installed at the bottom of the environment temperature control cabinet 1; the ice column model 3 is a tubular structure (with an inner diameter of 1 cm and a height of 5 mm); one end of the force sensor can contact the ice column model 3, and the other end is connected to the stepping push rod 4, which is the piston rod of the driving unit 6; the driving unit 6 is installed on the cooling table 5, and the driving unit 6 is one of a cylinder, an electric cylinder or a hydraulic cylinder.

[0236] During the test, the temperature of the cooling table was controlled at -25°C, the temperature of the ambient temperature control cabinet was set at -10°C, the sample 2 was placed on the side surface (upper surface) of the cooling table 5 located in the ambient temperature control cabinet, and the ice column model 3 was placed on the side surface (upper surface) of the sample away from the cooling table 5, and the axis of the ice column model 3 was perpendicular to the side surface (upper surface) of the sample 2 away from the cooling table 5. 1 ml of water was added to the ice column model; it was left for 10 minutes, and after the water cooled and frozen, the stepping push rod carrying the force sensor was adjusted to the section of the ice column model, with the center of the push rod head 1 to 2 mm away from the section, and the height was 1 mm away from the upper surface of the sample.

[0237] Start the test, control the stepping push rod and the force sensor to move at a speed of 0.2mm / s until the icicle causes interfacial shear fracture and moves, stop the push rod, and analyze and calculate the obtained force measurement data. The ice adhesion strength data is obtained by dividing the peak value of the instantaneous force during the fracture process by the frozen area of ​​the icicle (the area of ​​a circle with a diameter of 1cm).

[0238] Among them, sample 2 can be the anti-icing coating sample of each embodiment or comparative example.

[0239] (3) Photothermal effect

[0240] The coating sample was irradiated with a xenon lamp to simulate sunlight. 2 ), 10 cm from the coating surface, a cooling platform (i.e., the sample substrate, which can be Fig. 9 When the temperature of the cooling table in the homemade ice adhesion strength test device shown in the figure is -10°C, the surface temperature of the sample is measured using a Hikvision infrared thermal imager to test the photothermal effect of the sample.

[0241] (4) Robustness

[0242] Use Fig. 9 The homemade ice adhesion strength testing apparatus shown was used to conduct long-term robustness tests on the prepared samples.

[0243] (5) Electrical conductivity

[0244] The conductivity of the conductive grids obtained in the coating preparation process of each embodiment and comparative example was tested using the resistance range of a multimeter.

[0245] At the same time, the resistance of the coating was tested by the three-electrode method using an electrochemical workstation (model: CHI600 E), and the conductivity was obtained by simple calculation to measure the conductive effect of the coating.

[0246] (6) Lipophilicity

[0247] Drop 200ul of silicone oil (dimethyl silicone oil) on the coating surface and observe whether the silicone oil can diffuse and penetrate into the three-dimensional porous structure of the coating within 0-8s. If it can, it proves that the coating is lipophilic, otherwise it proves that the coating is not lipophilic. In addition, the contact angle of the oil drop on the coating surface over time was tested.

[0248] 2. Test results

[0249] Figure 5 is the resistance test value of the linear polypyrrole modified graphite wire conductive network in Example 1. Figure 1 It can be seen that the conductive network prepared in Example 1 has a good conductive effect, and the resistance value is 0 MΩ.

[0250] Figure 8 This is a comparison chart of the electrothermal performance of the anti-icing coating in Example 1. Figure 8 It can be seen that the anti-icing coating finally obtained in step (12) of Example 1 has a temperature of 40.7°C after 5 minutes when the voltage is applied to 5V, and when the voltage is increased to 10V, the temperature of the anti-icing coating rises to 108.8°C after 5 minutes, which proves that the anti-icing coating finally obtained in Example 1 has a good electrothermal effect.

[0251] Fig.10 This is a comparison chart of the ice adhesion strength of the anti-icing coating prepared in Example 1. Fig.10 It can be seen that Fig. 9 According to the test of the homemade ice adhesion strength testing device shown in the figure, the ice adhesion strength of the sample in Example 1 was 5.04 KPa, 4.34 KPa, and 4.03 KPa in three tests, respectively. Compared with the ice adhesion strength of 395.80 KPa of the sandblasted fiberglass sample, the decrease was more than 98.7%, and all showed good anti-ice properties.

[0252] Fig.11 This is a comparison chart of the ice adhesion strength of the anti-icing coating prepared in Example 2. Fig.11 It can be seen that Fig. 9According to the test of the homemade ice adhesion strength testing device shown in the figure, the ice adhesion strengths of the samples in Example 2 were 5.45 KPa, 5.10 KPa and 6.03 KPa respectively in three tests, which were decreased by more than 98.9% compared with the ice adhesion strength of 542 KPa of the acid-etched aluminum sheet sample, and all showed good anti-ice properties.

[0253] Fig.12 This is a characterization diagram of the photothermal performance of the anti-icing coating in Example 1. Fig.12 It can be seen that the anti-icing coating sample finally obtained in step (12) of Example 1 has a surface temperature of 30.4°C after being irradiated by one sun for 10 minutes when the substrate and ambient temperature are -5°C; when the substrate and ambient temperature are -10°C, the surface temperature can reach 27.8°C after being irradiated by one sun for 10 minutes; when the substrate and ambient temperature are -20°C, the surface temperature can reach 17.7°C after being irradiated by one sun for 10 minutes; when the substrate and ambient temperature are -30°C, the surface temperature can reach 4.8°C after being irradiated by one sun for 10 minutes; this shows that the anti-icing coating finally obtained in Example 1 has a good photothermal effect.

[0254] Fig.13 The low ice adhesion performance robustness of the anti-icing coating in Example 1. Fig.13 In the present invention, resin coating refers to the PDMS resin coating cured on the surface of the substrate; Fig.13 It can be seen that the anti-icing coating prepared in Example 1 of the present application maintains extremely low ice adhesion performance for at least 49 days.

[0255] Fig.14 The conductivity test of the coating sample of Comparative Example 1 is as follows. Fig.14 It can be seen that the coating does not conduct electricity when expanded microspheres without linear polypyrrole modification are added.

[0256] Fig.15 This is the light and heat performance test of the coating sample of Comparative Example 1. Fig.15 It can be seen that the surface temperature of the coating sample of Comparative Example 1 did not increase significantly under the irradiation of sunlight, and it did not have a good photothermal effect. Specifically, when the cooling stage temperature was set at -10°C, compared with the coating prepared by using linear polypyrrole-modified expandable microspheres in Example 1, the temperature of the sample of Comparative Example 1 only rose slightly (from -9.9°C to -8.2°C), proving that it had no photothermal effect, and its temperature rise was only due to the multiple reflection and retention effect of light by the porous surface, resulting in a short-term and weak temperature increase.

[0257] Fig.16This is a resistance test data diagram of the anti-icing coating prepared in Example 1. After testing and calculation, its resistance is about 742Ω. Combined with the size of the porous conductive network, the conductivity is calculated to be 7.42S / m, which shows that it has excellent conductivity.

[0258] Fig.17 This is a resistance test data diagram of the anti-icing coating prepared in Comparative Example 2. Fig.17 It can be seen that the resistance test results of the coating further prepared by using the conductive porous network prepared by expandable graphite without linear polypyrrole modification in Comparative Example 2 are about 9KΩ, and the conductivity is calculated to be 0.11S / m based on the size of the porous conductive network. Compared with the coating prepared by the conductive porous network prepared by linear polypyrrole modified graphite wire in Example 1, the conductivity is significantly worse, down 98.5%.

[0259] The test results of the coating conductivity of Examples 1, 4, 5 and Comparative Examples 3 and 4 are shown in Table 1.

[0260] Table 1 Test results of coating conductivity of Examples 1, 4, 5 and Comparative Examples 3 and 4

[0261]

[0262] It can be seen from Table 1 that when the amount of worm-like porous graphite wire is within the range of this application, the obtained coating has good conductivity; when the amount of worm-like porous graphite wire exceeds the range itself, the conductivity of the obtained coating decreases, especially when the amount of worm-like porous graphite wire exceeds the upper limit of this application, the conductivity of the coating decreases more significantly. This may be because when there are too many worm-like porous graphite wires, the normal proportion of conductive monomers cannot effectively modify all worm-like porous graphite wires, resulting in the prepared sample powder containing porous graphite wires that have not been polymerized and modified by the conductive monomer, which in turn reduces the conductivity, further affecting the conductivity of the coating prepared using the sample.

[0263] Fig.18 This is a comparison chart of the electrothermal performance of the coating prepared in Comparative Example 2. Fig.18 It can be seen that the coating further prepared by using the conductive porous network prepared by expandable graphite without linear polypyrrole modification in Comparative Example 2 has a significantly worse electrothermal effect. At a voltage of 10V, the temperature only rises from the initial 31.1°C to 40.5°C.

[0264] Fig.19 8, 9, Comparative Example 5 and Comparative Example 6 are scanning electron microscope images showing the cross-sectional porous structures. Fig.19It can be seen that the cross-sectional views of the anti-icing coatings prepared in Examples 8 and 9 are similar to those of the anti-icing coating prepared in Example 1, and the pores are interconnected and relatively uniform; however, in Comparative Example 5, due to the low content of L-Ppy-EM, the pores are dispersed and not interconnected, which affects the oil storage and anti-icing effects; in Comparative Example 6, due to the high content of L-Ppy-EM, the expandable microspheres are squeezed against each other and cannot expand effectively, which results in the failure to form uniform pores, which also affects the anti-icing effect of the coating.

[0265] Fig. 20 This is a test diagram of the lipophilicity of the anti-icing coating prepared in Example 1. Fig. 20 It can be seen that when 200ul of silicone oil (dimethyl silicone oil) is dropped on the surface of the anti-icing coating, the silicone oil quickly diffuses on the surface of the anti-icing coating and penetrates into the three-dimensional porous structure inside it within 0-8s, proving the high affinity of the anti-icing coating of Example 1 for silicone oil. At the same time, it is observed that the contact angle of the coating for the oil droplet is close to (is) 0° at 8s, further confirming that the coating has excellent oil affinity, that is, the oil droplet can be diffused and absorbed into its own three-dimensional porous structure within 8s.

[0266] To summarize, the preparation method of the anti-icing coating in the embodiment of the present application is to perform sandblasting or acid etching on the surface of the substrate (to achieve a uniform surface roughness level of about 10-30 μm), electroplating a linear poly first conductive organic monomer to modify a worm-like porous graphite wire with a porous template such as nickel foam, and then etching the porous template such as nickel foam to prepare a conductive porous network, and ultrasonically disperse the prepared linear poly second conductive organic monomer modified expandable microspheres in a high-temperature curing resin to fill the conductive porous network and solidify it, and further utilize the synergistic coupling of the expansion and contraction effect and photothermal effect of the conductive network and the linear modified expandable microspheres to achieve the preparation of a three-dimensional porous oleophilic anti-icing coating with excellent electrothermal and photothermal properties.

[0267] In the present application, the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0268] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A method for preparing an anti-icing coating having both photothermal and electrothermal properties, characterized in that: include: The expandable graphite is modified with a first conductive organic monomer, and then a first dispersion is performed to obtain a colloidal liquid; Using the colloidal liquid as an electrolyte, electroplating the porous template, and then etching away the porous template to obtain a conductive network; The expandable microspheres are modified with a second conductive organic monomer, and then second dispersed in a high temperature curing resin to obtain a dispersion; the high temperature curing resin comprises at least one of polydimethylsiloxane, an amorphous fluorine-containing polymer, polytetrafluoroethylene, and polychlorotrifluoroethylene; Placing the conductive network on the surface of a substrate, distributing the dispersion on the conductive network and the substrate, and then heating to expand, heating to shrink, and cooling in sequence to obtain a three-dimensional porous coating; The oily liquid is distributed on the surface and inner pores of the three-dimensional porous coating to obtain the anti-icing coating; the oily liquid includes at least one of silicone oil and perfluoropolyether oil.

2. The preparation method according to claim 1, characterized in that: The first conductive organic monomer and the second conductive organic monomer both include at least one of pyrrole, phenylacetylene, and aniline; And / or, the expandable microspheres are of a core-shell structure, the core is a hydrocarbon, and the shell is an acrylonitrile copolymer; And / or, the porous template includes at least one of foamed nickel, foamed copper, and foamed aluminum.

3. The preparation method according to claim 1, characterized in that: The method for modifying expandable graphite using a first conductive organic monomer comprises: The expandable graphite is subjected to a first expansion to obtain a worm-like porous graphite wire; dispersing the worm-like porous graphite wires in a first acidic solution containing a first template, then performing a first cooling, and adding the first conductive organic monomer to obtain a solution A; adding the first accelerator to the second acidic solution to obtain solution B; The solution A and the solution B are subjected to a first polymerization reaction to obtain a worm-like porous graphite line modified by a linearly polymerized first conductive organic monomer.

4. The preparation method according to claim 3, characterized in that: The temperature of the first expansion is 300-400°C; And / or, the usage ratio of the worm-like porous graphite wire and the first conductive organic monomer is: every 100 μl of the first conductive organic monomer corresponds to 500-700 mg of the worm-like porous graphite wire; And / or, the first template includes at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and hexadecyltrimethylammonium sulfate; and / or, the first acidic solution and the second acidic solution both include at least one of hydrochloric acid, hydrofluoric acid, and nitric acid; And / or, the temperature after the first cooling is (-4)-2°C; and / or, the first accelerator comprises at least one of ammonium persulfate, potassium persulfate, and benzoyl peroxide; And / or, the temperature of the first polymerization reaction is (-4)-2°C, and the time of the first polymerization reaction is 10-14h.

5. The preparation method according to claim 1, characterized in that: The method for modifying expandable microspheres using a second conductive organic monomer comprises: dispersing the expandable microspheres in a third acidic solution containing a second template, then performing a second cooling, and adding the second conductive organic monomer to obtain a solution C; adding the second accelerator to the fourth acidic solution to obtain solution D; The solution C and the solution D are subjected to a second polymerization reaction to obtain expandable microspheres modified by a linearly polymerized second conductive organic monomer.

6. The preparation method according to claim 5, characterized in that: The usage ratio of the expandable microspheres and the second conductive organic monomer is: every 100 μl of the second conductive organic monomer corresponds to 500-700 mg of the expandable microspheres; And / or, the second template includes at least one of hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, and hexadecyltrimethylammonium sulfate; And / or, the third acidic solution and the fourth acidic solution both include at least one of hydrochloric acid, hydrofluoric acid, and nitric acid; And / or, the temperature after the second cooling is (-4)-2°C; and / or, the second accelerator comprises at least one of ammonium persulfate, potassium persulfate, and benzoyl peroxide; And / or, the temperature of the second polymerization reaction is (-4)-2°C, and the time of the second polymerization reaction is 10-14h.

7. The preparation method according to claim 1, characterized in that: The first dispersant comprises at least one of ethanol, deionized water, and methanol; and / or, the concentration of the product of the first conductive organic monomer modifying the expandable graphite in the first dispersed dispersion is 10-20 mg / ml; And / or, the second dispersion is carried out in a diluted high temperature curing resin, wherein the diluent comprises at least one of tetrahydrofuran, toluene, dichloromethane and n-hexane; and / or, the content of the product of the second conductive organic monomer modifying the expandable microspheres in the dispersion of the second dispersion is 4-5 wt %; And / or, the mass ratio of the high temperature curing resin to the expandable microspheres modified with the second conductive organic monomer is 10:0.8-10:

1.

8. The preparation method according to claim 1, characterized in that: The electroplating process conditions include: the negative electrode is the porous template, the positive electrode is ITO-coated conductive glass, the distance between the negative electrode and the positive electrode is 0.5-1.5 cm, the applied voltage is 40-60 V, and the electroplating time is 15-25 min; And / or, the etching adopts ferric chloride solution, and the etching time is 20-28h; And / or, the method for preparing the anti-icing coating further comprises the steps of sequentially performing ultrasonic cleaning and plasma cleaning on the porous template before electroplating the porous template; And / or, the method for preparing the anti-icing coating further comprises the step of performing surface sandblasting or acid etching on the substrate before placing the conductive network on the substrate surface; And / or, the method for preparing the anti-icing coating further comprises the step of surface treating the three-dimensional porous coating before distributing the oily liquid on the surface and inner pores of the three-dimensional porous coating; And / or, the method for preparing the anti-icing coating further comprises the step of preheating the conductive grid and the substrate on which the dispersion is distributed before the heating expansion; And / or, the temperature of the heating expansion is 100-130° C., and the time of the heating expansion is 3-6 hours; And / or, the temperature of the heating shrinkage is 140-160°C; and / or, the heating and shrinking is performed until the product after the expandable microspheres are modified by the second conductive organic monomer shrinks to at least the original size or ruptures; And / or, the substrate is selected from at least one of a metallic material, a non-metallic material, an inorganic material, an organic material or a composite material.

9. An anti-icing coating, characterized in that: The method is described in any one of claims 1 to 8.

10. Use of the anti-icing coating according to claim 9 in the fields of electricity, transportation, communication or aviation.

Citation Information

Patent Citations

  • Ice-resistant coating as well as preparation method and application thereof

    CN116179079A

  • Photo-thermal super-hydrophobic anti-icing and deicing coating and preparation method thereof

    CN116376414A